Preparation of Microcrystalline Cellulose from Cotton and its Evaluation as Direct Compressible Excipient in the Formulation of Naproxen Tablets - Setu, Md Nurul Islam; Mia, Md Yeunus; Lubna, Nur Jaharat; Chowdhury, Abu Asad (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Microcrystalline cellulose (MCC) was prepared by acid hydrolysis from the cellulose purified from the cotton. Chemical assay, determination of degree of polymerization (DP) and FT-IR confirm the identification of prepared microcrystalline cellulose. The FT-IR spectrum of synthesized MCC is very similar to that of Avicel® PH- 102, a commercial direct compression excipient, at consideration of both band position and intensity. The degree of polymerization (DP) of prepared MCC and Avicel PH102, determined from the value of intrinsic viscosity, were 210 and 240, respectively. The tableting properties of prepared MCC was excellent while formulating naproxen tablet. The hardness and friability of the tablets prepared from MCC was 5.33 ± 0.45 kg and 0.077%, respectively which were comparable to the tablets prepared from marketed Avicel PH102 having hardness and friability 7.35 ± 0.41 kg and 0.063%, respectively. The disintegration time of tablet prepared from MCC and Avicel PH102 was 8.25 ± 0.41 min and 4.50 ±0.28 min, respectively. Again, the tablets prepared from MCC and Avicel PH102 showed more than 90% and 98% dissolution, respectively as per the USP specified medium. All these data indicate that the hardness, friability, disintegration and dissolution properties of tablets prepared by using our MCC comply with the USP specifications. This makes the prepared MCC as a promising candidate for direct compressible excipient of tablet. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21899 Dhaka Univ. J. Pharm. Sci. 13(2): 187-192, 2014 (December)